Jumping pepper and electrons in the shoe: using physical artefacts in a multilingual science class. Issue 14 (21st September 2020) - Ünsal, Zeynep; Jakobson, Britt; Wickman, Per-Olof; Molander, Bengt-Olov
ABSTRACT: This article concerns how teachers can use physical artefacts as mediating means to support emergent bilingual students' learning in science class. The data consist of non-participant observations in a Swedish 3rd grade (9–10 years old) class working with electricity. All students were bilingual, but in different minority languages and the teacher was monolingual in Swedish. The study focused on four students, all of whom had Turkish as their minority language. The findings show that the teacher used physical artefacts in two different ways. First, the physical artefacts implied that the students experienced the science content by actually seeing it. The students talked about their observations in everyday language, which the teacher then drew on to introduce how the phenomena or process in question could be expressed in scientific language. Second, when students' proficiency in the language of instruction limited their possibilities to make meaning, using physical artefacts enabled them to experience unfamiliar words as related to the science content and thus learn their meaning. The findings contribute to knowledge concerning how teachers can create learning contexts where physical artefacts are used to mediate scientific meaning.